An analysis of errors in the written English compositions of Trinidadian English Creole speakers - Winer, Lise (1982)
This study examined the written compositions of 448 Trinidadian secondary school students in a Creole/Standard learning situation. The sample included a geographic and ethnic cross-section at two grade levels--the beginning and end of secondary school. Each student wrote two compositions, controlled for discourse function. A comprehensive error analysis scheme was developed and all errors in the corpus were coded on several criteria, including error type and attribution of error source. Results of the data analysis showed significant levels of negative transfer from Creole to English. Significant differences were found between some sociolinguistic groups for several types of error rates
Keywords: Error analysis